PETROLOGIC EVIDENCE FOR SEA-LEVEL DROP IN LATEST PERMIAN IN JIANGXI PROVINCE, CHINA AND ITS MEANINGS FOR THE MASS EXTINCTION - Wu Y.S.; Jiang H.X.; Fan J.S.; Yang W. (My University, 2006)
A new-found Permian-Triassic boundary section in Xiushui, Jiangxi Province, China shows evidence for sea-level drop during the latest Permian. Evidence for sea-level drop was preserved in a 2.1 m thick interval of limestone, and is 1 m from the P-T boundary. The basal 0.1 m of this interval is a reddish sparry-cemented grainstone. The grains are rounded, dolomitized, all having a black coating. Microprobe analysis indicates that the coating is limonite, which indicates a weathering event in subaerial environments after a sea-level drop event. The internal structure of most grains has been destroyed by diagenesis. Some remained structures of foraminifers and fusulinids. So, this bed is formed before the mass extinction. The 2.0 m thick bed overlying the reddish grainstone is a dedolomitized limestone. The shapes of some original finely-crystalline dolomite rhombus were preserved. The occurrence of dedolomitization is generally related to meteoric water. So, this bed recorded a sea-level drop event. Fossils in this bed are simple: fusulinids and large foraminifers such as Colaniella are absent. It is clear that mass extinction began before this bed. The 1 m thick limestone between the dedolomitized bed and the P-T boundary is composed of grainstone and lime mudstone. Study of this section reached two points: (1) sea-level drop occurred in latest Permian; (2) The end-Permian mass extinction began in the earliest episode of the sea-level drop event. Thus, we cannot exclude the possibility that the mass extinction was caused by a dramatic environmental change which triggered the end-Permian sea-level drop.
Keywords: DEDOLOMITIZATION; END-PERMIAN; MASS EXTINCTION; PERMIAN-TRIASSIC BOUNDARY; SEA-LEVEL DROP; Мезозой::Триасовая; Палеозой::Пермская; Mesozoic::Triassic; Paleozoic::Permian